1978
DOI: 10.1515/ijsl.1978.16.11
|View full text |Cite
|
Sign up to set email alerts
|

Sanskrit in the Pre-Islamic Sociolinguistic Context of South Asia

Abstract: 1.2. The chronology is misleading, first of all in that Classical Sanskrit and Prakrit clearly were contemporary with each other (cf. section 2 below). Moreover, at least since Weber (1847) it has been argued that Sanskrit and Prakrit really were sister dialects, both descended from the same ancestor, Vedic, and preserving different features of that ancestral dialect. (Cf. Wackernagel 1896:xxv-xxvi for a good summary and discussion of the Brought to you by | University of Michigan Authenticated Download Date |… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…4 De fait, le prakrit est une forme d'indo-âryen plus évoluée que le sanskrit classique. 5 VoirHock & Pandharipande (1978, p. 13), Pinault (1989a. 6 C ' est dans les oeuvres de dramaturgie, où les variétés linguistiques sont distribuées selon le rang social des personnages, que cette situation diglossique se manifeste avec le plus d ' évidence.…”
unclassified
“…4 De fait, le prakrit est une forme d'indo-âryen plus évoluée que le sanskrit classique. 5 VoirHock & Pandharipande (1978, p. 13), Pinault (1989a. 6 C ' est dans les oeuvres de dramaturgie, où les variétés linguistiques sont distribuées selon le rang social des personnages, que cette situation diglossique se manifeste avec le plus d ' évidence.…”
unclassified
“…For some discussion of the status of Sanskrit as a spoken language in ancient times, seeHock and Pandharipande (1976), and for an account of language-death phenomena in spoken Sanskrit today, seeHock (1983).4 Though it is not possible here even to approach exhaustiveness concerning a listing of all generative work on Sanskrit since 1976, see footnote 1 and note the publication ofHock (1991) in which several studies are to be found on Sanskrit syntax from various perspectives, including more recent generative approaches, as well as fairly comprehensive bibliography on relevant syntactic studies.…”
mentioning
confidence: 99%